Overexpression of Hypoxia-Inducible Factor-1α Is a Predictor of Poor Prognosis in Cervical Cancer: A Clinicopathologic Study and a Meta-analysis. Issue 6 (1st July 2014) - Huang, Miaoling; Chen, Qing; Xiao, Jianpeng; Yao, Tingting; Bian, Lijuan; Liu, Changhao; Lin, Zhongqiu
Abstract : Background: Published data on the prognostic value of hypoxia-inducible factor-1α (HIF-1α) expression in cervical cancer are conflicting and heterogeneous. We aimed to derive a more precise estimation of them. Methods: We conducted a clinicopathologic study in 74 patients with early-stage cervical cancer treated through surgery and performed a meta-analysis among patients with cervical cancer of all stages to estimate the prognostic importance of HIF-1α expression for disease-free survival (DFS) and overall survival (OS). Expression of HIF-1α was evaluated through immunohistochemistry. Results: A positive nuclear expression of HIF-1α was found in 94.6% of all specimens. There were significant associations between HIF-1α expression and International Federation of Gynecology and Obstetrics stage ( P = 0.024), tumor size ( P = 0.003), and anemia ( P = 0.010), respectively. Log-rank tests revealed significant correlations between HIF-1α expression, International Federation of Gynecology and Obstetrics stages, tumor grade, tumor size and DFS/OS, respectively. The multivariate Cox regression analyses revealed HIF-1α overexpression and high tumor grade to be independent predictors for impaired DFS (HIF-1α overexpression: hazard ratio [HR], 2.67; 95% confidence interval [CI], 1.10–6.47; high tumor grade: HR, 5.56; 95% CI, 1.47–21.13) and OS (HIF-1α overexpression: HR, 2.57; 95% CI, 1.06–6.23; high tumor grade: HR, 6.23; 95% CI, 1.49–25.97). The results of 10 studies indicated that HIF-1α overexpression predicted poor DFS (HR, 1.98; 95% CI, 1.22–3.21) and OS (HR, 2.58; 95% CI, 1.86–3.56) for cervical cancer. Conclusions: The present clinicopathologic study and meta-analysis showed that HIF-1α overexpression is associated with poor survival of cervical cancer and emphasized the importance of HIF-1α as a predictor for cervical cancer.